2020
DOI: 10.1177/1089253220901665
|View full text |Cite|
|
Sign up to set email alerts
|

Intravenous Fluid Management Practices in Kidney Transplant Patients: A Multicenter Observational Cohort Pilot Study

Abstract: Background Limited evidence exists with regard to best practices in fluid management during kidney transplantation, which may directly affect the incidence of DGF. The authors of this study embarked on a collaborative observational multicenter pilot study to evaluate fluid administration practices in different transplant centers, with a focus on the relationship between total administered crystalloid volume and its association with DGF. Methods Twenty consecutive kidney transplant patients were included from 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 31 publications
0
7
1
Order By: Relevance
“…The intraoperative crystalloid volume was similar in patients who developed or did not develop DGF, and this was similar to the findings of a recent multicenter pilot study. [ 16 ] In the present study, CVP was slightly elevated at the end of surgery in the non-DGF group, but this was not statistically conclusive. Studies on CVP as a volume guide in kidney transplant showed inconsistent results, with many studies advising maximal hydration[ 17 ] and high CVP to ensure good graft function,[ 18 ] whereas other studies observed an association between high CVP and DGF[ 5 ] and advised against supranormal volume loading, especially in cardiac patients with poor myocardial function.…”
Section: Discussioncontrasting
confidence: 80%
“…The intraoperative crystalloid volume was similar in patients who developed or did not develop DGF, and this was similar to the findings of a recent multicenter pilot study. [ 16 ] In the present study, CVP was slightly elevated at the end of surgery in the non-DGF group, but this was not statistically conclusive. Studies on CVP as a volume guide in kidney transplant showed inconsistent results, with many studies advising maximal hydration[ 17 ] and high CVP to ensure good graft function,[ 18 ] whereas other studies observed an association between high CVP and DGF[ 5 ] and advised against supranormal volume loading, especially in cardiac patients with poor myocardial function.…”
Section: Discussioncontrasting
confidence: 80%
“…This is in accordance with a national trend. 12 The marked increase in delayed graft function between 2005 and 2013 (Supplemental Digital Content 3, http:// links.lww.com/ALN/C656) has previously been reported. 26 This is attributed to the increasing utilization of expanded criteria donors in an effort to meet the high demand of kidney donations.…”
Section: Fluid Management In Kidney Transplantmentioning
confidence: 77%
“…[5][6][7]9,10 Based on these results, some institutions and providers worldwide have already shifted away from normal saline in kidney transplantation. 12 In contrast, the effects of normal saline administration on clinical outcomes, especially on kidney graft function, remain unclear. In fact, none of the cited randomized trials was powered to detect a meaningful difference in function of the grafted kidney.…”
Section: Editor's Perspectivementioning
confidence: 99%
“…Optimum perioperative fluid administration with adequate intravascular volume maintenance is essential to improve outcomes in critically ill patients, prevent acute organ failure or dysfunction, and improve immediate graft function after KTA and SPKT [ 19 , 21 , 31 , 32 , 33 , 34 , 35 ]. Determination of the perfect amount of fluid therapy is highly challenging in critically ill patients, as well as in the perioperative phase during operations with a high fluid turnover.…”
Section: Discussionmentioning
confidence: 99%